92.3k views
5 votes
2x -y=6 and x+y=-3 solving systems by substitution

User Alibaba
by
4.4k points

1 Answer

6 votes


x+y=-3\qquad\text{subtract y from both sides}\\\\x=-y-3\\\\\text{Substitute it to the equation}\ 2x-y=6:\\\\2(-y-3)-y=6\\\\-2y-6-y=6\qquad\text{add 6 to both sides}\\\\-3y=12\qquad\text{divide both sides by (-3)}\\\\\boxed{y=-4}\\\\\text{Put the value of y to the equation}\ x=-y-3:\\\\x=-(-4)-3\\\\x=4-3\\\\\boxed{x=1}\\\\Answer:\ \boxed{x=1\ and\ y=-4\to(1,\ -4)}

User GermainGum
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.